Physical attractiveness and health comment on Weeden and Sabini (2005). [article]. - Grammer, K.
Evolutionary behavioral biology suggests that certain characteristics of the human face and body are important for mate preferences and are therefore subject to sexual selection. J. Weeden and J. Sabini identify a number of weaknesses in the association between traits' attractiveness and health. In contrast, the authors argue that (a) studies on preferences for physical characteristics that rely on 1 trait permit only limited interpretation, (b) limitations placed on J. Weeden and J. Sabini's review exclude important associations, (c) there are misconceptions in their treatment of some traits, and (d) their selected literature provides an inaccurate picture regarding effect size. The authors suggest that future research in this field should seek conceptual and methodological constancy in trait selection and in the evaluation of attractiveness- and health-related traits. -- (from the author)